AN ANALYSIS OF DIFFERENCES IN HOTEL, RESTAURANT AND ENTERTAINMENT TAX RECEIPTS BEFORE AND DURING THE COVID-19 PANDEMIC - Nunik Lestari Dewi; Ita Salsalina Lingga; Suying Sumantri (LPPM STIE Muhammadiah Bandung, 2022)
The COVID-19 pandemic has an impact on the economic downturn on a national scale, which also impacts a number of regions in Indonesia, one of which is the Garut Regency. The business sectors affected by the COVID-19 pandemic include the hotel, restaurant, and entertainment sectors. This study aimed to analyze hotel tax, restaurant tax, and entertainment tax revenues in Garut Regency before and during the COVID-19 pandemic. The analysis was to determine the growth rate and effectiveness of the Garut Regency Hotel Tax, Restaurant Tax, and Entertainment Tax and analyze the differences between before and during the COVID-19 pandemic. The study was conducted using a limited sample, namely 2018-2019 before the pandemic and 2020-2021 during the pandemic. The sample was collected using purposive sampling with judgment criteria. The data obtained was retrieved using archival data collection techniques and analyzed through descriptive and other tests. The results show that the growth rate of hotel tax and restaurant tax is more fluctuating than the entertainment tax. The effectiveness of the hotel and restaurant tax showed that it was equally effective before and during the pandemic, while the entertainment tax was more effective before the pandemic. There are differences in hotel, restaurant, and entertainment tax receipts before and during the pandemic.